1970
DOI: 10.3126/nje.v1i1.4107
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Blood Pressure among Youth in Ajman, UAE

Abstract: BackgroundYouth is a vulnerable group for developing almost all life-style related diseases. The present cross-sectional study was conducted to assess the determinants of blood pressure among entry year students in a medical university in Ajman, United Arab Emirates.Materials and Methods  One hundred and ten students from Gulf Medical University, Ajman, UAE participated in the study. A pretested structured questionnaire was used for data collection. Predictive Analytic Software 17 was used for data analysis. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…These differences may be due to the racial differences of the study subjects. In this study mean BMI of the study subjects was found to be 21.68 ± 3.55, Kavita Chaudhry et al, 2012 11 found it to be 22.33 ± 3.83 and Sreedharan J et al, 2010 21 found it to be 24.9 ± 5.7, which were similar. Mean BMI of the male and female subjects was found to be 21.79 ± 3.40 and 21.58 ± 3.70 respectively in this study whereas Ujunwa et al, 2013 22 found it to be 19.81 ± 3.61 and 21.16 ± 3.29 respectively, which were similar.…”
Section: Discussionsupporting
confidence: 71%
“…These differences may be due to the racial differences of the study subjects. In this study mean BMI of the study subjects was found to be 21.68 ± 3.55, Kavita Chaudhry et al, 2012 11 found it to be 22.33 ± 3.83 and Sreedharan J et al, 2010 21 found it to be 24.9 ± 5.7, which were similar. Mean BMI of the male and female subjects was found to be 21.79 ± 3.40 and 21.58 ± 3.70 respectively in this study whereas Ujunwa et al, 2013 22 found it to be 19.81 ± 3.61 and 21.16 ± 3.29 respectively, which were similar.…”
Section: Discussionsupporting
confidence: 71%
“…[24][25][26][27] A recent study done among youth at Ajman observed that there is 14% increased chance for getting pre-hypertension or hypertension for a unit increase in BMI. 28 Berenson et al reported high BMI as one of the strongest risk factors of hypertension. 29 The present study also supported the observation made by other authors with regard to overweight or obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Amma et al observed that overweight or obese adolescents had 5.7 times more risk of developing hypertension than normal or underweight adolescents [ 15 ]. A recent study done among youth in the United Arab Emirates reported a 14% higher risk of pre-hypertension or hypertension with an increase in BMI per unit [ 20 ].…”
Section: Discussionmentioning
confidence: 99%